Synopsis of the genus Erythropterus Melzer, 1934 (Coleoptera: Cerambycidae, Heteropsini) - Napp, Dilma Solange; Monné, Miguel A. (Zootaxa, 2005)
The genus Erythropterus Melzer, 1934 is redescribed, E.cuissi, new species is described from Brazil (Rondônia) and a key to species is provided.